Molybdenum disulfide semiconductor composite hydrogel for solar water purification and preparation method thereof

By using a composite hydrogel coated with MoS2 hollow nanospheres and PDA nanowires in solar water purification technology, the problems of high energy consumption and evaporation-collecting efficiency in the existing technology are solved, and efficient photothermal conversion and stable evaporation efficiency are achieved, which is suitable for small applications and industrial integration.

CN116606516BActive Publication Date: 2025-05-02NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310408860.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2025-05-02
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

The existing solar water purification technology has problems such as high energy consumption, high demand for functional materials, and complex equipment. The evaporation-collecting efficiency is insufficient, making it difficult to achieve small-scale applications and industrial integration.

Method used

MoS2 hollow nanospheres are used as photothermal semiconductor nanoparticles, and are coated through PDA nanowires and embedded in a three-dimensional porous PVA hydrogel network to form a molybdenum disulfide semiconductor composite hydrogel, improving photothermal conversion performance and evaporation stability.

Benefits of technology

It achieves efficient photothermal conversion, stable longitudinal water transfer capacity and solar evaporation efficiency, reduces preparation costs and equipment complexity, and is suitable for small applications and industrial integration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116606516B_ABST
    Figure CN116606516B_ABST
Patent Text Reader

Abstract

The present invention discloses a molybdenum disulfide semiconductor composite hydrogel for solar water purification, belonging to the fields of solar water evaporation, nanomaterial synthesis, and polymer composite materials. The prepared semiconductor composite hydrogel has good photothermal conversion performance, longitudinal water transportation ability, and solar evaporation stability. The present invention prepares MoS2 hollow nanospheres with a fullerene-like structure by a liquid-phase reduction-high temperature annealing process, grows mutually entangled PDA nanowires on the surface of the MoS2 hollow nanospheres by a liquid-phase in-situ polymerization method, adjusts the polymerization time and solution ratio to control the thickness and density of the PDA nanowire layer, maximizes the thermal localization and activation effect of PDA on MoS2, and obtains a double-layer hollow nanosphere structure with optimal photothermal conversion ability and hydrophilicity. Use SAT to prepare a PVA porous hydrogel matrix with a three-dimensional porous structure, and uniformly disperse the MoS2@PDA double-layer hollow nanospheres in the three-dimensional framework structure to obtain a three-dimensional solar water evaporation material with excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical fields of semiconductor nanocomposite hydrogel synthesis, seawater desalination and sewage treatment, and specifically relates to a molybdenum disulfide semiconductor composite hydrogel for solar water purification and a preparation method thereof. Background Art

[0002] With the continuous development of modern social life and industrial manufacturing, the demand for freshwater resources is increasing day by day. Nowadays, the reserves and utilization efficiency of freshwater resources have become one of the most important factors restricting the economic development of many regions and countries. Developing freshwater resources in the natural environment is obviously the main way to deal with the shortage of freshwater, but it is obviously not a long-term solution to the shortage of water for life and industry in the future. Since the 2010s, seawater desalination and sewage treatment have gradually come into people's view. In fact, the distillation-condensation method for water purification has a very long history. Even if this can indeed solve the shortage of freshwater resources to some extent, the high energy demand and low collection efficiency are still shortcomings that cannot be ignored. Therefore, it is urgent to develop a water purification solution with low energy consumption, simple and convenient operation and large-scale integrated operation. At present, the mainstream methods of seawater desalination and sewage treatment include membrane filtration, multiple adsorption, heating evaporation, reverse osmosis, etc. However, various methods have the disadvantages of high functional material requirements, reliance on fine functional equipment or excessive energy consumption, so researchers gradually turn their attention to renewable and large-scale primary energy-solar energy. Converting solar energy into thermal energy to evaporate and collect seawater or sewage has become one of the most direct, effective and promising methods to solve the problem of freshwater resources.

[0003] In recent years, researchers have reported various photothermal composite hydrogels with good photothermal conversion capabilities or complex light absorption micro-nano structures. There are endless structural and material performance designs for evaporation, heat preservation, and water transport functions, but they are often restricted by high preparation costs or insufficient evaporation-collection efficiency, making it difficult to develop in the direction of small-scale applications or industrial integration. In addition, researchers also pay more attention to evaporation materials or the photothermal effects of evaporation materials, while ignoring the important role of condensation-collection structures in the entire evaporation-collection process. How to efficiently promote the spontaneous condensation and collection of hot steam, and how to reduce the secondary evaporation of the collected purified water, will become the future development direction of solar photothermal evaporation water purification devices.

[0004] At present, the photothermal conversion materials with relatively good performance mainly include metal materials, semiconductor materials, carbon-based materials and some polymer materials with plasmon effects. Among the many photothermal conversion materials, metal materials and polymer materials are limited by their spectral absorption range and poor stability under long-term application. Although carbon-based materials have good physical and chemical properties and three-dimensional structures, they are difficult to apply on a large scale due to their high prices and difficult preparation. In comparison, semiconductor materials have extremely high research value due to their advantages such as adjustable band gap, wide solar spectrum absorption range, low cost and strong durability. In addition, semiconductor materials can also have complex micro-nano structures similar to carbon-based materials through reasonable molding processes and preparation methods. In the field of solar-driven interfacial evaporation, research on semiconductor materials mainly focuses on materials such as CuO and MXenes, cobalt and nickel oxides. Most of the previously reported semiconductor photothermal material conversions only involve the direct addition of commercial materials and simple in-situ synthesis, and do not involve the control of the three-dimensional micro-nano structure of semiconductor materials during the synthesis process to broaden the spectral absorption range, reduce diffuse emission, and enhance the photothermal conversion capacity. In addition, research on broadening the spectral absorption range of MoS2 semiconductor materials and enhancing the bonding stability with the hydrogel matrix through in-situ polymerization coating of PDA has not been reported.

[0005] Hydrogel materials have also been extensively studied in recent years. Their abundant hydroxyl groups give them exceptionally good hydrophilicity, and they also have the ability to form intermediate water to reduce evaporation enthalpy and improve evaporation efficiency. Hydrogel materials can not only produce rich three-dimensional pore structures through simple process control during the preparation process, but also have the basic easy processing and reusability of polymer materials. Based on the above characteristics, cross-linked hydrogel materials can serve as an excellent platform for solar-driven interfacial evaporation. Most of the reported hydrogel materials focus on their hydrophilicity and swelling ability. In some studies, complex liquid nitrogen directional cooling or light-induced processes are used to produce neatly arranged longitudinal pore structures to enhance water transport capacity. However, not only are the processes and preparation conditions harsh and complex, but they also lose too much heat due to the high-speed transmission of water inside them. Summary of the invention

[0006] The present invention provides a molybdenum disulfide semiconductor composite hydrogel for solar water purification and a preparation method thereof. The prepared semiconductor composite hydrogel has good photothermal conversion performance, water transport capacity and solar evaporation stability, a simple preparation process, the required experimental equipment and experimental environment are safe and easy to obtain, the reaction conditions are mild, the molding cycle is short and it is easy to process special shapes.

[0007] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0008] A molybdenum disulfide semiconductor composite hydrogel for solar water purification, wherein the composite hydrogel uses MoS2 hollow nanospheres as photothermal semiconductor nanoparticles, the MoS2 hollow nanospheres are externally coated with PDA nanowires that are entangled with each other to form a network structure, and the MoS2 hollow nanospheres externally coated with PDA nanowires are embedded in a three-dimensional porous PVA hydrogel network.

[0009] A method for preparing a molybdenum disulfide semiconductor composite hydrogel for solar water purification comprises the following steps:

[0010] Step 1: Synthesize MoS2 hollow nanospheres as photothermal semiconductor nanoparticles by liquid phase reduction-high temperature annealing;

[0011] Step 2: coating the surface of the MoS2 hollow nanospheres obtained in step 1 with a porous PDA layer by regulating the pH, concentration and dispersion of the particles;

[0012] Step 3: The composite double-layer hollow nanospheres obtained in step 2 are embedded into the three-dimensional porous PVA hydrogel network by a solution blending method to obtain a molybdenum disulfide semiconductor composite hydrogel.

[0013] In the above steps, step 1 specifically includes the following steps:

[0014] (1) 0.5-1 mmol of ammonium tetrathiomolybdate ((NH4)2MoS4) was added to 80 mL of N-methylpyrrolidone (NMP) and a clear solution was obtained after ultrasonic stirring for 3 h;

[0015] (2) 5-10 mL of N2H4·H2O was added dropwise to the clear solution while stirring, and the solution was heated to 80°C and stirred continuously under gentle reflux for 12 h. After cooling naturally, the dark brown precipitate was collected by centrifugation, washed with ethanol and deionized water in sequence, and then dried in a vacuum chamber at 80°C overnight;

[0016] (3) The material obtained in step (2) was placed in a nitrogen atmosphere at a rate of 100 mL min -1 Flow rate: 5℃min -1 The porcelain boat was heated to 800°C and cooled to room temperature after 2 h to obtain a black powder.

[0017] Step 2 specifically includes the following steps:

[0018] ① Prepare Tris (tris(hydroxymethylaminomethane)·HCl buffer with pH=8.5: Dissolve 0.6057 g of Tris (white powder) in 50 ml of deionized water for later use, dilute 12 mol / L concentrated hydrochloric acid to 0.1 mol / L, take 14.7 ml, mix with Tris solution, add deionized water and dilute to 100 ml to obtain the target buffer;

[0019] ② Take 0.2-0.4g dopamine hydrochloride, dissolve it in 40ml Tris·HCl buffer, add 0.4g prepared MoS2 hollow nanospheres, and polymerize under high-speed stirring for 12h;

[0020] ③ The black suspension obtained after polymerization was centrifuged in deionized water at 10000rpm for 10min, and then the black precipitate was taken out three times, washed once with ethanol, and dried in vacuum at room temperature overnight;

[0021] Step 3 specifically includes the following steps:

[0022] ① Add 5g PVA particles into 40ml, 80℃ deionized water and stir for 1h to obtain a clear and transparent PVA aqueous solution;

[0023] ② Without stopping stirring, cool naturally to below 60°C, add 0.6-0.8g of prepared MoS2@PDA composite hollow nanospheres, continue stirring for 30 minutes, use a cell disruptor to sonicate for 30 minutes, and then continue stirring;

[0024] ③ Add 3.5-5 g of formaldehyde solution (37 wt%) to the mixture, stir for 3 min, then add 1-2 ml of concentrated hydrochloric acid (12 mol / L), and continue stirring for 3 min;

[0025] ④ The mixed solution was poured into a customized plastic / Teflon mold and placed in an oven to cure at 80 °C for 3 h. After natural cooling and slight freezing, it was taken out of the mold, rinsed with ethanol and soaked in deionized water (DIW) to remove the reaction residues to obtain a black hydrogel composite hydrogel.

[0026] Beneficial effects: The present invention provides a semiconductor molybdenum disulfide composite hydrogel for solar water purification and a preparation method thereof, wherein liquid phase reduction-high temperature annealing is used to synthesize MoS2 hollow nanospheres with a fullerene-like structure as efficient photothermal semiconductor nanoparticles, dopamine hydrochloride is in-situ grown and polymerized to coat the MoS2 hollow nanospheres to grow entangled PDA nanowires, dopamine hydrochloride is self-assembled through solution oxidation polymerization to form a network structure on the outside of MoS2 to obtain MoS2@PDA composite nanoparticles, and a porous PDA layer is coated on the surface of the hollow spheres by regulating pH and the concentration and dispersion of the particles to improve hydrophilicity and broaden the spectral absorption, activate the MoS2 surface electron layer, and utilize the internal hollow structure of the spherical particles to make the solar The light produces multiple reflections to achieve the purpose of enhancing the photothermal conversion capacity; the material composition of the water transport matrix is ​​a PVA porous hydrogel material with a three-dimensional porous structure prepared by SAT (self-assembly template method), and the composite double-layer hollow nanosphere photothermal particles are embedded into the three-dimensional porous PVA hydrogel network by a solution blending method. The PVA network has hydroxyl groups arranged densely on the internal three-dimensional network, which has extremely strong hydrophilicity and can form a three-dimensional random channel for rapid water transport from bottom to top. The introduction of HCHO cross-linking agent does not affect the distribution and overall number of hydroxyl groups, and can improve the stability and uniformity of the three-dimensional porous skeleton without affecting the overall hydrophilicity. On the other hand, it also enhances the overall water transport capacity of the hydrogel matrix, and the evaporation rate can reach 4.7kg·m -2 ·h -1 ; The prepared semiconductor composite hydrogel has good photothermal conversion performance, longitudinal water transport capacity and solar evaporation stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The actual picture of MoS2@PDA double-layer hollow nanosphere powder prepared in Example 1 and Example 2 of the present invention;

[0028] Figure 2 This is a physical picture of the heterogeneous molding of MoS2@PDA / PVA composite hydrogel prepared in Example 1 of the present invention;

[0029] Figure 3 This is a physical picture of the columnar MoS2@PDA / PVA composite hydrogel prepared in Example 2 of the present invention;

[0030] Figure 4 SEM images of MoS2 hollow nanospheres (left) and MoS2@PDA double-layer hollow nanospheres (right) in Example 1 of the present invention;

[0031] Figure 5 This is a cross-sectional SEM scanning electron microscope image of the MoS2@PDA / PVA composite hydrogel in Example 1 of the present invention in a completely dry state;

[0032] Figure 6 This is a physical picture of the MoS2@PDA / PVA composite hydrogel in Example 1 of the present invention under the test state;

[0033] Figure 7 This is a water evaporation curve of the MoS2@PDA / PVA composite hydrogel in Example 1 of the present invention under 1 sun intensity irradiation;

[0034] Figure 8 This is a graph showing the 8-hour long-term steady-state evaporation curve of the MoS2@PDA / PVA composite hydrogel in Example 1 of the present invention in real seawater (taken from the East China Sea) under 1 sun irradiation;

[0035] Fig. 9 This is a test diagram of the salt resistance of the MoS2@PDA / PVA composite hydrogel in Example 1 of the present invention;

[0036] Fig.10 This is the infrared spectrum of the MoS2@PDA / PVA composite hydrogel in Example 1 of the present invention;

[0037] Fig.11 This is a UV-vis-NIR absorption curve diagram of the MoS2 hollow nanospheres and the MoS2@PDA double-layer hollow nanospheres in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments:

[0039] Example 1

[0040] A method for preparing a molybdenum disulfide semiconductor composite hydrogel for solar water purification comprises the following steps:

[0041] 0.5mmol ammonium tetrathiomolybdate ((NH4)2MoS4) was added to a 200mL beaker containing 80mL N-methylpyrrolidone (NMP); after ultrasonic stirring for 3h, the obtained clear solution was transferred to a 250mL three-necked flask, and 5.0mL N2H4·H2O was added dropwise to the flask under magnetic stirring; the flask was heated to 80℃ in an oil bath and stirred continuously under gentle reflux for 12h, cooled naturally and set aside; the black-brown precipitate was collected by centrifugation at 8000rpm, washed with ethanol and deionized water in sequence, and then dried in a vacuum chamber at 80℃ overnight; ⑤ the above materials were placed in a porcelain boat and kept in the center of a quartz tube in a typical tubular furnace, and then the tube was purged with nitrogen for 20min to remove oxygen; nitrogen was added at 100mL·min -1 Flow rate: 5℃min -1Heat the porcelain boat to 800℃, and after 2h, let the furnace cool to room temperature to obtain black powder. Prepare Tris (trishydroxymethylaminomethane)·HCl buffer with pH=8.5, take 0.6057g of Tris (white powder) and dissolve it in 50ml deionized water for use, dilute 12mol / L concentrated hydrochloric acid to 0.1mol / L, take 14.7ml, mix it with Tris solution, and add deionized water to dilute to 100ml to obtain the target buffer; take 0.2g dopamine hydrochloride, dissolve it in 40ml Tris·HCl buffer, add 0.4g prepared MoS2 hollow nanospheres, and polymerize under high-speed stirring for 12h; the black suspension obtained after polymerization is centrifuged in deionized water at 10000rpm for 10min, then take the black precipitate three times, wash it once with ethanol, and vacuum dry it at room temperature overnight. 5 g of PVA particles were added to 40 ml of deionized water at 80 ° C and stirred for 1 hour to obtain a clear and transparent PVA aqueous solution; without stopping stirring, it was naturally cooled to below 60 ° C, and 0.6 g of the prepared MoS2@PDA composite hollow nanospheres were added, and stirring was continued for 30 minutes. After ultrasonication with a cell disruptor for 30 minutes, stirring was continued; 3.5 g of formaldehyde solution (37 wt%) was added to the mixture, and after stirring for 3 minutes, 1 ml of concentrated hydrochloric acid (12 mol / L) was added, and stirring was continued for 3 minutes; the mixture was poured into a customized plastic / Teflon mold, placed in an oven at 80 ° C for curing for 3 hours, and after natural cooling and slight freezing, it was taken out from the mold, rinsed with ethanol and soaked in DIW to remove the reaction residues to obtain a black hydrogel composite hydrogel.

[0042] The actual pictures of MoS2@PDA double-layer hollow nanosphere composite hydrogel and MoS2@PDA / PVA composite hydrogel obtained by the above method are shown in Figure 1 As shown in Figure 2, a double-layer hollow nanosphere semiconductor material with a black powder appearance was obtained. After the above steps, it was evenly dispersed into the hydrogel matrix, and a special-shaped hydrogel photothermal evaporation component as shown in the figure was obtained by customizing the mold. The cross-sectional SEM scanning electron microscope image of the obtained MoS2@PDA / PVA composite hydrogel material in a completely dry state is shown in Figure 2. Figure 5 As shown in the figure, it can be seen that a uniform three-dimensional porous network is formed, in which the pore structure with a size of 1 to 10 μm is produced when the intermediate water and free water are separated from the hydrogel matrix, and the pore structure above 50 μm is produced when the bound water is forcibly extracted from the polymer network. The three-dimensional network structure of this pore size can provide stable longitudinal water transport through strong capillary action and combined with surface hydrophilicity.

[0043] Example 2

[0044] A method for preparing a molybdenum disulfide semiconductor composite hydrogel for solar water purification comprises the following steps:

[0045] 1mmol ammonium tetrathiomolybdate ((NH4)2MoS4) was added to a 200mL beaker containing 80mL N-methylpyrrolidone (NMP); after ultrasonic stirring for 3h, the obtained clear solution was transferred to a 250mL three-necked flask, and 10mL N2H4·H2O was added dropwise to the flask under magnetic stirring; the flask was heated to 80℃ in an oil bath and stirred continuously under gentle reflux for 12h, cooled naturally and set aside; the black-brown precipitate was collected by centrifugation at 8000rpm, washed with ethanol and deionized water in sequence, and then dried in a vacuum chamber at 80℃ overnight; ⑤ the above materials were placed in a porcelain boat and kept in the center of a quartz tube in a typical tubular furnace, and then the tube was purged with nitrogen for 20min to remove oxygen; nitrogen was added at 100mL·min -1 Flow rate: 5℃min -1 Heat the porcelain boat to 800℃, and after 2h, let the furnace cool to room temperature to obtain black powder. Prepare Tris (trishydroxymethylaminomethane)·HCl buffer with pH=8.5, take 0.6057g of Tris (white powder) and dissolve it in 50ml deionized water for use, dilute 12mol / L concentrated hydrochloric acid to 0.1mol / L, take 14.7ml, mix it with Tris solution, and add deionized water to dilute to 100ml to obtain the target buffer; take 0.4g dopamine hydrochloride, dissolve it in 40ml Tris·HCl buffer, add 0.4g prepared MoS2 hollow nanospheres, and polymerize under high-speed stirring for 12h; the black suspension obtained after polymerization is centrifuged in deionized water at 10000rpm for 10min, then take the black precipitate three times, wash it once with ethanol, and vacuum dry it at room temperature overnight. 5 g of PVA particles were added to 40 ml of deionized water at 80 ° C and stirred for 1 hour to obtain a clear and transparent PVA aqueous solution; without stopping stirring, it was naturally cooled to below 60 ° C, and 0.8 g of the prepared MoS2@PDA composite hollow nanospheres were added, and stirring was continued for 30 minutes. After ultrasonication with a cell disruptor for 30 minutes, stirring was continued; 5 g of formaldehyde solution (37 wt%) was added to the mixture, and after stirring for 3 minutes, 2 ml of concentrated hydrochloric acid (12 mol / L) was added, and stirring was continued for 3 minutes; the mixture was poured into a customized plastic / Teflon mold, placed in an oven at 80 ° C for curing for 3 hours, and after natural cooling and slight freezing, it was taken out from the mold, rinsed with ethanol and soaked in DIW to remove the reaction residues to obtain a black hydrogel composite hydrogel.

[0046] The MoS2@PDA double-layer hollow nanosphere composite hydrogel and MoS2@PDA / PVA composite hydrogel obtained by the method of the present invention are shown in FIG. Figure 1As shown in Figure 3, the prepared black powder is evenly dispersed in the precursor mixed solution during the solution mixing process before hydrogel molding, and can be placed in different molds during thermal cross-linking or cut after molding to prepare a shape that is conducive to interfacial photothermal evaporation.

[0047] Figure 4 The SEM image of MoS2@PDA composite powder shows that hollow spheres with a diameter of about 200 nm and double-layer hollow spheres coated with PDA are obtained through the above preparation process. Figure 5 It can be seen that a uniform three-dimensional porous network is formed, in which the pore structure with a size of 1 to 10 μm is generated when the intermediate water and free water are separated from the hydrogel matrix, and the pore structure above 50 μm is generated when the bound water is forcibly extracted from the polymer network. This three-dimensional porous network can provide stable water transport for the photothermal evaporation process; Figure 6 The actual pictures before and after the illumination test under the light intensity of 1 sun, there is no morphological change on the evaporation surface due to lack of water supply or overheating, which proves the evaporation stability of the material in the present invention; Figure 7 The water evaporation rate of the MoS2@PDA / PVA composite hydrogel material in the present invention was tested and reached an extremely high 4.66 kg·m under 1 sun intensity. -2 ·h -1 , almost reaching the highest value of solar-driven interfacial evaporation rate that can be achieved by hydrogel composites reported so far; Figure 8 The evaporation stability of MoS2@PDA / PVA composite hydrogel material under continuous irradiation for one day (8 h) was tested, and its evaporation rate remained at 4.2 kg·m after 8 h of irradiation. -2 ·h -1 ; Fig. 9 The actual pictures before and after the salt resistance test, sodium chloride powder was directly spread on the surface of the columnar hydrogel composite material. After 8 hours of evaporation, the surface salt particles almost disappeared due to the salt diffusion exchange in the porous network inside the hydrogel, indicating that the composite material in the present invention has good autonomous salt discharge ability, can be used for solar interface driven evaporation in high-salinity seawater or high-concentration inorganic pollutant water, and has good application prospects in solar seawater desalination and sewage treatment; Fig.10 The infrared absorption spectrum of MoS2@PDA / PVA composite hydrogel material is shown, where 1000cm -1 CH peak at 1600cm -1 The catechol hydroxyl peak at 3400 cm -1 The OH peak at indicates the successful compounding of this material; Fig.11The UV-vis-NIR absorption curves of MoS2@PDA double-layer hollow nanosphere composites and pure MoS2 hollow nanosphere materials are shown, proving that the hollow structure significantly improves the light absorption capacity of MoS2 semiconductor materials in the ultraviolet and visible light regions.

[0048] The present invention not only utilizes the hollow structure of MoS2 hollow nanospheres to make the incident light refract and reflect multiple times, but also greatly reduces the diffuse reflection on the MoS2 surface through the in-situ polymerization coating of MoS2 hollow nanospheres by PDA. In addition, PDA itself has a light absorption rate of more than 95% in the near-infrared region. Its photothermal effect on the MoS2 surface can activate the energy band structure of MoS2, thereby coupling to produce a stronger photothermal effect. A three-dimensional porous cross-linked hydrogel is prepared by a self-assembled soft template method based on thermochemical cross-linking, and its longitudinal water transport capacity is as high as the evaporation rate of the surface semiconductor composite material. The degree of matching minimizes internal heat loss under the condition of satisfying water supply, and at the same time has good durability, simple process, and short production cycle; and the hydroxyl groups in the hydrogel network can form multiple and stable hydrogen bonds with the PDA layer, which enhances the stability of the photothermal composite particles in the hydrogel network. Due to the catechol hydroxyl structure of PDA, it has excellent physical adhesion ability on the surface of most materials. The double-layer hollow sphere nanoparticles in the present invention have significant advantages in terms of binding ability with hydrophilic water-transporting matrix and sunlight utilization compared with other interface evaporation materials. In addition, the polyvinyl alcohol, dopamine hydrochloride, etc. involved in the present invention are all low-cost and easily available environmentally friendly materials, which will not burden the natural environment during production, processing and use, and have a relatively ideal prospect for industrial application.

[0049] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention, and these improvements should also be regarded as within the protection scope of the present invention.

Claims

1. A method for preparing a molybdenum disulfide semiconductor composite hydrogel for solar water purification, characterized in that: The following steps are involved: Step 1: Synthesizing MoS2 hollow nanospheres by liquid phase reduction-high temperature annealing, specifically comprising the following steps: (i) 0.5-1 mmol of ammonium tetrathiomolybdate ((NH4)2MoS4) was added to 80 mL of N-methylpyrrolidone and a clear solution was obtained after ultrasonic stirring for 3 h; (ii) Add 5-10 mL N2H4·H2O dropwise to the clear solution while stirring, heat to 80°C, and stir continuously under gentle reflux for 12 h. After cooling naturally, collect the dark brown precipitate by centrifugation, wash, and dry. (iii) heating the material obtained in step (ii) to 800° C. in a nitrogen atmosphere and cooling to room temperature after 2 h to obtain a black powder, namely MoS2 hollow nanospheres; Step 2: coating the surface of the MoS2 hollow nanospheres obtained in step 1 with a porous PDA layer by regulating the pH, concentration and dispersion of the particles; Step 3: The composite double-layer hollow nanospheres obtained in step 2 are embedded into the three-dimensional porous PVA hydrogel network by a solution blending method to obtain a molybdenum disulfide semiconductor composite hydrogel.

2. The method for preparing the molybdenum disulfide semiconductor composite hydrogel for solar water purification according to claim 1, characterized in that: The nitrogen flow rate in step (iii) was 100 mL min – 1 , the heating rate is 5℃ / min.

3. The method for preparing the molybdenum disulfide semiconductor composite hydrogel for solar water purification according to claim 1, characterized in that: Step 2 specifically includes the following steps: ① Prepare Tris·HCl buffer with pH=8.5; ② Take 0.2-0.4 g dopamine hydrochloride, dissolve it in 40 ml tris(hydroxymethyl)aminomethane·HCl buffer, add 0.4 g MoS2 hollow nanospheres, and polymerize under high-speed stirring for 12 h; ③ The black suspension obtained after the polymerization was centrifuged and the black precipitate was taken out and vacuum dried at room temperature to obtain MoS2@PDA composite hollow nanospheres.

4. The method for preparing the molybdenum disulfide semiconductor composite hydrogel for solar water purification according to claim 3, characterized in that: Step ① specifically includes the following steps: dissolving 0.6057 g of tris(hydroxymethyl)aminomethane in 50 ml of deionized water, diluting 12 mol / L concentrated hydrochloric acid to 0.1 mol / L, mixing 14.7 ml of the tris(hydroxymethyl)aminomethane solution with deionized water and diluting the mixture to 100 ml to obtain the target buffer solution.

5. The method for preparing the molybdenum disulfide semiconductor composite hydrogel for solar water purification according to claim 1, characterized in that: Step 3 specifically includes the following steps: (a) 5 g of PVA particles were added to 40 ml of deionized water at 80 °C and stirred for 1 h to obtain a clear and transparent PVA aqueous solution; (b) without stopping stirring, naturally cool to below 60 °C, add 0.6-0.8 g of prepared MoS2@PDA composite hollow nanospheres, continue stirring for 30 min, and continue stirring after ultrasonication for 30 min; (c) Add 3.5-5 g of formaldehyde solution to the mixture, stir for 3 min, then add 1-2 ml of concentrated hydrochloric acid and continue stirring for 3 min; (d) The mixed solution was poured into a mold and cured at 80 °C for 3 h. After natural cooling and slight freezing, it was taken out of the mold and rinsed with ethanol and soaked in deionized water (DIW) to remove the reaction residues to obtain a black composite hydrogel.

6. The method for preparing the molybdenum disulfide semiconductor composite hydrogel for solar water purification according to claim 5, characterized in that: In step (c), the concentration of the formaldehyde solution is 37 wt %, and the concentration of the concentrated hydrochloric acid is 12 mol / L.

7. The molybdenum disulfide semiconductor composite hydrogel for solar water purification prepared by the method according to any one of claims 1 to 6, characterized in that: The composite hydrogel uses MoS2 hollow nanospheres as photothermal semiconductor nanoparticles. The MoS2 hollow nanospheres are coated with PDA nanowires that are entangled with each other to form a network structure. The MoS2 hollow nanospheres coated with PDA nanowires are embedded in a three-dimensional porous PVA hydrogel network.

8. The molybdenum disulfide semiconductor composite hydrogel for solar water purification according to claim 7, characterized in that: The MoS2 hollow nanospheres have a fullerene-like structure.

9. The molybdenum disulfide semiconductor composite hydrogel for solar water purification according to claim 7, characterized in that: The PVA hydrogel network has hydroxyl groups arranged at a high density on the internal three-dimensional network, which can form three-dimensional random channels for rapid water transport from bottom to top.

Citation Information

Patent Citations

  • Photothermal conversion textile based on self-assembled molybdenum disulfide nanospheres and preparation method of photothermal conversion textile

    CN112680955A

  • Preparation method and application of molybdenum disulfide carbon nanotube polyvinyl alcohol-based photo-thermal material

    CN115058056A